"Who is going to take care of these grandkids if I go?": End-of-life planning by caregivers in grandparent-headed households. Issue 3 (16th March 2023) - Freeman, Jessica D.; Elton, Jessica; Lambert South, Andrea
Abstract: This qualitative study applied thematic analysis to semi-structured interviews with 15 key informants who self-identified as primary caregivers to at least one grandchild. Using Family Systems Theory and Theory of Planned Behavior as guiding frameworks, this study reports grandparent caregivers' end-of-life planning behaviors while illuminating factors influencing these behaviors. The analysis revealed two themes related to grandparents' communicative behaviors surrounding end-of-life planning (formal and informal behaviors) and four themes related to factors that influence grandparents' end-of-life planning (emotional paradoxes, legal/custodial conundrums, concerns about child wellbeing, and resources needed to plan). Findings extend end-of-life planning literature to often overlooked nontraditional family populations.